REMOVABLE AND NON-REMOVABLE DENTAL PROSTHESES (World Bulletin of Public Health, 2023)
In this article we will have an understanding of dental prostheses and their types, non-removable and removable prostheses
Keywords: Prosthesis; dental procedures; one crown